COLOR AND SHAPE HARMONY: METHODOLOGY FOR DEVELOPING CREATIVE ACTIVITIES IN SCHOOLS - Abdurahmonova Dildora Nizomjon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores effective methodologies for developing creative activities in schools through the study of color and shape harmony. It highlights pedagogical approaches that enhance students’ visual perception, aesthetic literacy, and compositional skills. Practical exercises, interactive tasks, and project-based learning are emphasized as strategies to engage students, stimulate creative thinking, and foster independent artistic expression.